Mountain biking injuries in children and adolescents - Aleman, K. B.; Meyers, M. C. (Sports Medicine, 2010)
Over the last decade, the sport of mountain biking has experienced extensive growth in youth participation. Due to the unpredictable nature of outdoor sport, a lack of rider awareness and increased participation, the number of injuries has unnecessarily increased. Many believe that the actual incidence of trauma in this sport is underestimated and is just the `tip of the iceberg`. The most common mechanism of injury is usually attributed to downhill riding and forward falling. Although rare, this type of fall can result in serious cranial and thoraco-abdominal trauma. Head and neck trauma continue to be documented, often resulting in concussions and the possibility of permanent neurological sequelae. Upper limb injuries range from minor dermal abrasions, contusions and muscular strains to complex particular fracture dislocations. These are caused by attempting to arrest the face with an outstretched hand, leading to additional direct injury. Common overuse injuries include repeated compression from the handlebars and vibration leading to neurovascular complications in the hands. Along with reports of blunt abdominal trauma and lumbar muscle strains, lower extremity injuries may include various hip/pelvic/groin contusions, patellofemoral inflammation, and various muscle strains. The primary causes of mountain biking injuries in children and adolescents include overuse, excessive fatigue, age, level of experience, and inappropriate or improperly adjusted equipment. Additional factors contributing to trauma among this age group involve musculoskeletal immaturity, collisions and falls, excessive speed, environmental conditions, conditioning and fitness status of the rider, nonconservative behavioural patterns, and inadequate medical care. The limited available data restrict the identification and understanding of specific paediatric mountain biking injuries and injury mechanisms. Education about unnecessary risk of injury, use of protective equipment, suitable bikes and proper riding technique, coupled with attentive and proper behaviour, are encouraged to reduce unnecessary injury. This article provides information on the causation and risk factors associated with injury among young mountain bikers, and recommendations to minimize trauma and enhance optimal performance and long-term enjoyment in this outdoor sport.